SAM PELONG Dalam Perspektif Budaya Musik Minangkabau - Tety Darlenis (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
Sampelong is not only thought of as an instrument, but also has deep cultural meanings, function and symbol for Minangkabau society. For example, the process ofmaking the instrument is associated with the goal for what the instrument is meant. Moreover, the instrument, that is thought of as the inheritance of Pre-Hindu culture, used to have an bad image in the society, that is used for sending â€œblack magicâ€. Nowadays, sampelong exists in different contexts.